2002
DOI: 10.1053/jlts.2002.33457
|View full text |Cite
|
Sign up to set email alerts
|

Role of gender and race mismatch and graft failure in patients undergoing liver transplantation

Abstract: Previous data have suggested an increased risk of graft failure in male recipients of female livers, and in nonwhite recipients of orthotopic liver transplantation. United Network for Organ Sharing records of liver transplantations from 1992 through 2000 with at least one follow-up visit were reviewed. Analysis of these data was performed with proportional hazards regression, controlling for follow-up time, age, gender, ethnicity, number of comorbidities, functional status at time of transplant, and status 1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 19 publications
5
67
1
Order By: Relevance
“…However, the graft failure rate was worse in male recipients receiving female donor organs (12.9%; P ϭ .003). 31 …”
Section: Gendermentioning
confidence: 99%
“…However, the graft failure rate was worse in male recipients receiving female donor organs (12.9%; P ϭ .003). 31 …”
Section: Gendermentioning
confidence: 99%
“…While female-male discordance in LT has been shown to be associated with increased risk of graft loss in one UNOS database analysis, 9 other results have been contradictory. 1,10,11 It is possible that female donor status is a surrogate for an as yet unidentified variable that influences graft survival.…”
Section: Discussionmentioning
confidence: 76%
“…1 In addition to various factors that were found to be significant predictors of graft outcome, some studies have revealed that donor-recipient sex mismatch (in particular female donor-male recipient) negatively affects graft survival. [5][6][7] However, other studies have reported either that male-female mismatch had no effect or attributed the outcome difference to other donor factors. 8,9 Specifically in 1 US registry study of more than 28 000 liver transplants, donor quality, as measured by the Donor Risk Index, 10 1 Niklas Buescher, 1 Andreas Andreou, 1 Marcus Bahra, to be the real cause of inferior graft outcome in female donor-male recipient combinations.…”
Section: Introductionmentioning
confidence: 86%